AGRN promotes lung adenocarcinoma progression by activating Notch signaling pathway and acts as a therapeutic target - Huan Zhang; Jiaqi Liang; Tao Lu; Ming Li; Guangyao Shan; Guoshu Bi; Mengnan Zhao; Xing Jin; Qun Wang; Zhengcong Chen; Cheng Zhan (Elsevier, 2023)
Lung cancer is the main reason for cancer-associated death globally, and lung adenocarcinoma (LUAD) is the most prevalent subtype of lung cancer. Recently, AGRN is considered playing an vital role in the development of some cancers. However, the regulatory effects and mechanisms of AGRN in LUAD remain elusive. In this study, we clarified the significant upregulation of AGRN expression in LUAD by single-cell RNA sequencing combined with immunohistochemistry. Besides, we confirmed that LUAD patients with high AGRN expression are more susceptible to lymph node metastases and have a worse prognosis by a retrospective study of 120 LUAD patients. Next, we demonstrated that AGRN directly interact with NOTCH1, which results in the release of the intracellular structural domain of NOTCH1 and the subsequent activation of the NOTCH pathway. Moreover, we also found that AGRN promotes proliferation, migration, invasion, EMT and tumorigenesis of LUAD cells in vitro and in vivo, and that these effects are reversed by blocking the NOTCH pathway. Furthermore, we prepared several antibodies targeting AGRN, and clarify that Anti-AGRN antibody treatment could significantly inhibit proliferation and promote apoptosis of tumor cells. Our study highlights the important role and regulatory mechanism of AGRN in LUAD development and progression, and suggests that antibodies targeting AGRN have therapeutic potential for LUAD. We also provide theoretical and experimental evidence for further development of monoclonal antibodies targeting AGRN.